(untitled) (Research, Society and Development, 2021)
Objective: to analyze the scientific evidence regarding hemodynamic changes presented by the critically ill patient during a bed bath. Methods: This is an integrative literature review, after using the PICO strategy, we built the following guiding question “What are the possible hemodynamic changes presented by critically ill patients related to bed baths?”. With the reading and application of the selection criteria, five articles were used. Results: the articles could be grouped into two categories - Hemodynamic changes related to the type of bath and the main hemodynamic changes found during the bath, regardless of the type of bath. The reviewed articles obtained significant results regarding the hemodynamic variables: body temperature, respiratory (RR) and heart (HR), Blood Pressure (BP), cardiac index, Central Venous Pressure (CVP) and systolic volume. Conclusion: The need for more detailed investigations to better clarify the impacts of bed baths for critically ill patients was evidenced, for nursing care based on scientific and safe evidence.